Mentalitas Peserta Didik, Pendidikan Transformatif Paulo Freire - Titus Tara, S.Ag., M.Th (Sekolah Tinggi Pastoral Atma Reksa Ende, Jalan Gatot Subroto, KM 3. Tlp./Fax (0381) 250012, 2016)
The basic problems in shaping the mentality of High School students in South East Nusa Tenggara (Nusa Tenggara Timur – NTT) at present time are proactive attitude in classroom, time discipline, learning enthusiasm, and willingness to give oneself to be educated by teachers. What is the root cause of the problem? Nowadays, education is supposedly no more applying banking system, which is like someone deposits a great number of money in a bank, so it is a theacher deposits a huge piled of knowledgeinto student’s brain. This surely for the student will be very much saturated and exhausting. On the contrary, it should be ‘teacher becomes student and student becomes teacher’ teaching-learning system (Paulo Freire). Therefore,it is very imperative for the Catechistto develop a dialogal teaching system,providing wide space for the prosess of action-reflection-action to work properly for the liberation and empowerment of student as true human being.